USER TÉCINO: TECHNOLOGY TRANSFER, EMERGING TECHNICAL ACTORS, AND BRAZILIAN OPEN-SOURCE SOFTWARE - Choi, Beatrice (AoIR Selected Papers of Internet Research, 2015)
The initial steps Brazil made in regards to the technology transfer and local production of computers took place in the early 1970s, manifesting as state-driven technology policy emerging from a set of national security concerns. At the time, the Brazilian Navy was operating its ships using British Ferranti computers, a fact which triggered the military’s growing awareness of its dependence on foreign technologies, which according to sociologist Peter Evans “became thereafter a central justification for the national computer policy” (Evans, 69). Consequently, Brazilian policies issue standards on international technology transfer to open the market to Brazilian consumers, and foster protectionist measures for local computer production to provide an incubating space for Brazilian innovators (Tigre 1983, Evans 1986, Schwartzman 1988). Without attempting to conflate the trend from proprietary hardware towards programmed software, I argue that Brazil’s evolving technology policies, rotating cast of technical actors, and local computer production establish the premise for a robust software culture to take root in the present.